Research and Practice on the Collaborative Education System for the Innovation and Entrepreneurship of E-commerce Major - Wang, Yan; Tang, Bin (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
With the continuous promotion of education and teaching reform in China, combined with the characteristics of e-commerce major, the training mode of combining entrepreneurship education and professional education can better enhance the competitiveness of students and expand the employment path. Based on the current situation of e-commerce innovation and entrepreneurship education, this paper explores the "specialty+entrepreneurship" integrated e-commerce collaborative education system, and provides reference suggestions for the optimization of e-commerce innovation and entrepreneurship education in application-oriented universities. It is of great significance to alleviate the pressure of social employment and promote the development of entrepreneurial economy and the construction of innovative country.